Effects of age on physical and technical performance in National Basketball Association (NBA) players - Kalén, A.; Pérez-Ferreirós, A.; Costa, P. B.; Rey, E. (Research in Sports Medicine, 2021)
This study evaluated the effects of age on physical and technical game performance for different positions in professional basketball players. In this cross-sectional study, a total of 25,523 individual match observations were undertaken on players from the 2018-19 NBA season. The players were classified into four age groups (19-22 years, 23-25 years, 26-29 years, and 30-42 years). Differences in physical and technical match performance were analysed for the following variables: distance covered, average speed, minutes played, points scored and playing efficiency. The results showed that players older than 30 covered shorter distance and had lower average speed than younger players, that guards and forwards older than 26 played more minutes per game than younger ones, and that guards older than 26 scored more points and were more efficient than younger one, while centres age 23-25 scored more points per games than centres older than 30. In conclusion, physical performance declined with age, and while playing time and technical performance generally remained stable or increased, especially for guards. However, there was some evidence of decline for centres.